Interpunktionen i runehåndskriftet AM 28 8vo af Skånske Lov - Danielsen, Martin Sejer (Danske Studier, 2024)
The medieval Danish manuscript AM 28 8vo containing int. al. the Scanian Law is written entirely in runes. An innovation in the runic punctuation system has been made during the transmission of runes to Latin manuscript culture. The word dividers consisting of two dots above each other are sometimes expanded with more dots, so that three, four or five dots are set in a line above each other. These expansions may very well have been made by the writer himself and/or a corrector, but the possibility that later readers made some expansions cannot be ruled out. Although these expanded word dividers appear with some irregularity, the function of them is to divide chapters into sentences, clauses and other more or less independent parts. As such the expanded word dividers have a function similar to the punctuation found in a closely related manuscript of the Scanian Law written in the Latin alphabet. This is a discovery that has not previously been made.